Synthesis of a novel 2D zinc(ii) metal–organic framework for photocatalytic degradation of organic dyes in water. Issue 47 (22nd November 2019) - Dong, Jian-Peng; Shi, Zhen-Zhen; Li, Bo; Wang, Li-Ya
Abstract : A new 2D zinc(ii ) metal–organic framework exhibits efficient photocatalytic activity and recyclability towards the degradation of organic dyes in the absence of any photosensitizer or cocatalyst. Abstract : A novel 2D zinc(ii ) metal–organic framework, formulated as [Zn(L)(H2 O)]·H2 O (1 ) (H2 L = 4-(pyridine-4-yl) phthalic acid), has been successfully obtained under solvothermal conditions. This metal–organic framework (MOF) material exhibits efficient photocatalytic activity towards the degradation of organic dyes in the absence of any photosensitizer or cocatalyst. Its catalytic performance for rhodamine B (RhB) and methyl orange (MO) degradation was superior to most reported MOFs with a degradation efficiency of 98.5% for RhB and 83.8% for MO within 120 min in the absence of H2 O2, which could be attributed to its high efficiency in generating ·O2 − (an effective oxidant for the degradation of dyes). The possible mechanism of the reaction was discussed in detail. In addition, 1 shows stable catalytic efficiency after five reaction cycles, which indicates that 1 exhibits efficient catalytic activity and good reusability toward the degradation of organic dyes, enabling it to be a potential candidate for environmental governance.